Hong Kong Med J 2020
DOI: 10.12809/hkmj198126
|View full text |Cite
|
Sign up to set email alerts
|

Brain death in children: a retrospective review of patients at a paediatric intensive care unit

Abstract: Among patients in paediatric intensive care units (PICUs), death is sometimes inevitable despite advances in treatment. Some PICU patients may have irreversible cessation of all brain function, which is considered as brain death (BD). This study investigated demographic and clinical differences between PICU patients with BD and those with cardiopulmonary death. Methods: All children who died in the PICU at a university-affiliated trauma centre between October 2002 and October 2018 were included in this retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“… 13 In most of the multicenter studies evaluating pediatric BD, multiple trauma and traumatic brain injury, hypoxic ischemic injury resulting from cardiac arrest, and intracranial hemorrhages were found to be the leading causes of BD in the pediatric population. 11 ,14- 16 The reason for this difference in etiologies between our study and most of the existing literature, may be that some pediatric cases with BD that occurred after traumatic brain injury had been admitted to the neurosurgical intensive care unit or other departments in our hospital, and therefore they were excluded from our study. The median age in our study was about 7 years, similar to that reported by Gündüz and Joffe.…”
Section: Discussionmentioning
confidence: 84%
“… 13 In most of the multicenter studies evaluating pediatric BD, multiple trauma and traumatic brain injury, hypoxic ischemic injury resulting from cardiac arrest, and intracranial hemorrhages were found to be the leading causes of BD in the pediatric population. 11 ,14- 16 The reason for this difference in etiologies between our study and most of the existing literature, may be that some pediatric cases with BD that occurred after traumatic brain injury had been admitted to the neurosurgical intensive care unit or other departments in our hospital, and therefore they were excluded from our study. The median age in our study was about 7 years, similar to that reported by Gündüz and Joffe.…”
Section: Discussionmentioning
confidence: 84%
“…6,7 However, parents or carers sometimes demand futile treatment for patients in the PICU. 8 A hospital ethics committee may help resolve such matters where the requested treatment may not be in the best interest of the patient. However, even members of an ethics committee may hold different opinions, making ethical decisions difficult.…”
Section: Respect For Autonomymentioning
confidence: 99%
“…1 However, ROSC within 30 minutes is usually required for a favourable outcome. 2,3 We performed a literature search to determine the longest time to ROSC and survival rates of OHCA in children (Table ). Out-of-hospital cardiac arrest in children has a poor prognosis and prolonged in-hospital resuscitation beyond 30 minutes does not improve survival.…”
Section: Survival Of Out-of-hospital Cardiac Arrest Following a Retur...mentioning
confidence: 99%